(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article speaks about language represents of the concept «Cult». The «cult» concept is one of the concepts that has its own place in the spiritual and cultural system of people. Cult by the abstract description is a complicated concept. Today linguistics expanded scope of the language study as a spiritual and cultural wealth of the nation. Through various language units it’s possible to acquaint with the life experience of the people, their customs and knowledge, rituals, life, worldview, faith and believe. Research is closely associated with a range of linguistic anthropology, psychology, philosophy, logic, mythology, ethnography, etc., the consideration of cult phraseologisms of Turkic languages in various aspects prove, it as a new perspective. Spiritual culture is cognized with the concepts of human’s view on the environment, religious cognition, beliefs and superstitions, character, ability, etc.